A method for testing the degree of solubility

By using light transmittance and viscosity testing methods during the toughening synthesis of matrix resin, the degree of dissolution of toughened particles is accurately judged, which solves the problem that the degree of dissolution of toughened particles cannot be qualitatively judged during the toughening synthesis of matrix resin, and improves the impact resistance of composite materials.

CN119780049APending Publication Date: 2025-04-08ZHONGFU SHENYING (SHANGHAI) TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411921304.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

During the toughening and synthesis of matrix resin, the degree of dispersion and dissolution uniformity of toughened particles cannot be qualitatively judged, which affects the impact resistance of composite materials.

Method used

A method for testing the degree of dissolution is provided, by dispersing the toughened particles into the resin composition under preset conditions, heating to a first preset temperature, forming the composition to be tested, and taking out a plurality of samples to be tested in time periods from the composition to be tested, and their light transmittance and viscosity are respectively tested to determine the degree of dissolution of the toughened particles.

Benefits of technology

Through the measurement of light transmittance and viscosity, this test method can accurately determine the degree of dissolution of toughened particles in the resin composition, solve the problems of inefficiency and inaccuracy of traditional methods, provide a fast and accurate assessment of the degree of dissolution, and guide the production process of resin-based composite materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119780049A_ABST
    Figure CN119780049A_ABST
Patent Text Reader

Abstract

The present disclosure provides a method for testing the degree of solubility, and the testing method includes: under preset conditions, dispersing toughening particles into a resin composition, heating the temperature to a first preset temperature to form a composition to be tested; taking out a plurality of samples to be tested from the composition to be tested at different time periods starting from the time when the temperature is raised to the first preset temperature; testing the transmittance of each sample to be tested respectively; testing the viscosity of each sample to be tested respectively; and determining the degree of solubility of the toughening particles in the composition to be tested according to the transmittance and viscosity of each sample to be tested. The method for testing the degree of solubility provided by the present disclosure determines the degree of solubility of the toughening particles in the composition to be tested by using the transmittance and viscosity of the composition to be tested which are easily measured, and effectively solves the problem that the degree of solubility of the toughening particles in the composition to be tested cannot be qualitatively judged, and the testing process is convenient and fast, and the test results are accurate, which can effectively provide guidance for the production process of resin-based composite materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of composite material preparation, and in particular to a method for testing the degree of solubility. Background Art

[0002] Carbon fiber reinforced composite materials have outstanding specific strength and specific modulus, strong designability, good fatigue resistance and corrosion resistance. Due to its excellent mechanical properties, it has been increasingly used as a high-performance material in various fields, especially in the aerospace industry. With the widespread use of carbon fiber reinforced composite materials in aircraft, how to improve the impact resistance and other properties of carbon fiber reinforced composite materials has gradually become a key research and development direction. Research on the matrix resin of carbon fiber reinforced composite materials is one of the hot topics.

[0003] Matrix resin toughening is to add thermoplastic resin toughening particles or toughening agents to thermosetting resins, and then prepare composite materials from the obtained prepregs. The main implementation method is to add thermoplastic resins during the synthesis of matrix resins or directly add thermoplastic resins to matrix resins to prepare prepregs, thereby improving the toughness of the matrix resin, which can effectively prevent the propagation of cracks and improve the impact resistance of composite materials. However, in the process of matrix resin toughening synthesis, there is a problem that the addition of toughening particles cannot be qualitatively judged in terms of the uniformity of dispersion and dissolution. Summary of the invention

[0004] In order to solve the problems existing in the related art, the present disclosure provides a method for testing the degree of solubility, and the testing method comprises:

[0005] Under preset conditions, the toughening particles are dispersed and added into the resin composition, and the temperature is raised to a first preset temperature to form a composition to be tested;

[0006] When the temperature is raised to the first preset temperature, a plurality of samples to be tested are taken out from the composition to be tested in different time periods;

[0007] Testing the light transmittance of each of the samples to be tested respectively;

[0008] Testing the viscosity of each of the samples to be tested respectively;

[0009] The dissolution degree of the toughening particles in the composition to be tested is determined according to the transmittance and viscosity of each of the samples to be tested.

[0010] In some embodiments of the present disclosure, determining the degree of dissolution of the toughening particles in the composition to be tested according to the transmittance and viscosity of each of the samples to be tested includes:

[0011] Determining whether the transmittance and the viscosity of the composition to be tested satisfy a linear relationship according to the transmittance and the viscosity of each of the samples to be tested;

[0012] When the transmittance and the viscosity satisfy the linear relationship, the dissolution degree of the toughening particles in the composition to be tested is determined according to a preset rule.

[0013] In some embodiments of the present disclosure, determining the degree of dissolution of the toughening particles in the composition to be tested according to a preset rule includes:

[0014] Determining the peak time when the transmittance and / or the viscosity reaches a peak value;

[0015] When the dissolution time is greater than or equal to the peak time, the dissolution of the toughening particles in the composition to be tested is complete; the dissolution time includes the time measured from the time when the temperature is raised to the first preset temperature.

[0016] In some embodiments of the present disclosure, the preset conditions include: the second preset temperature is 70-90°C.

[0017] In some embodiments of the present disclosure, the resin composition includes at least one of bisphenol A epoxy resin, bisphenol F epoxy resin, bisphenol S epoxy resin, AFG90 epoxy resin, AG80 epoxy resin and aminophenol-based trifunctional epoxy resin; and / or,

[0018] The toughening particles include at least one of polyetherimide, polyethersulfone, polyphenylene oxide, polyimide, polyetheretherketone and polyaryletherketone.

[0019] In some embodiments of the present disclosure, the particle size of the toughening particles is 50-500 um.

[0020] In some embodiments of the present disclosure, the step of taking out a plurality of samples to be tested from the composition to be tested at different time periods comprises:

[0021] The samples to be tested were taken out from the composition to be tested at 0 min, 20 min, 40 min, 60 min, 80 min and 90 min, respectively.

[0022] In some embodiments of the present disclosure, the method further comprises: when the resin composition comprises a plurality of resins, mixing the resins at 70-90° C. for 10-30 min to obtain the resin composition.

[0023] In some embodiments of the present disclosure, the step of testing the light transmittance of each of the samples to be tested comprises:

[0024] The transmittance of each of the samples to be tested was tested by a spectrophotometer at a preset wavelength of 780-390 nm and a scanning speed of 0.5-1 nm.

[0025] In some embodiments of the present disclosure, the step of testing the viscosity of each of the samples to be tested comprises:

[0026] The viscosity of each of the samples to be tested was tested by a rheometer at a heating rate of 1-3°C / min and at a temperature of 95-110°C.

[0027] The beneficial effects of the present disclosure include but are not limited to: the solubility test method provided by the present disclosure determines the solubility degree of the toughening particles in the test composition by means of the transmittance and viscosity of the test composition which can be easily measured, thereby effectively solving the problem that the solubility degree of the toughening particles in the test composition cannot be qualitatively judged, and the test process is convenient and fast, and the test results are accurate, which can effectively provide guidance for the production process of resin-based composite materials.

[0028] It is to be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present disclosure. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] The accompanying drawings incorporated into the specification and constituting a part of the specification illustrate embodiments of the present disclosure and are used together with the description to explain the principles of the embodiments of the present disclosure. In these drawings, similar reference numerals are used to represent similar elements. The drawings described below are some embodiments of the present disclosure, rather than all embodiments. For those skilled in the art, other drawings can be obtained based on these drawings without paying creative work.

[0030] Figure 1 The figure is a flow chart of a method for testing the degree of solubility according to an exemplary embodiment of the present disclosure;

[0031] Figure 2 It is a schematic diagram of the linear relationship between the transmittance and viscosity of the composition a to be tested according to an exemplary embodiment of the present disclosure;

[0032] Figure 3 It is a schematic diagram of the variation trend of the viscosity of the composition a to be tested with the sampling time and the variation trend of the transmittance with the sampling time according to an exemplary embodiment of the present disclosure;

[0033] Figure 4 Schematic diagram of the linear relationship between the transmittance and viscosity of the composition b to be tested according to an exemplary embodiment of the present disclosure;

[0034] Figure 5 It is a schematic diagram of the variation trend of the viscosity of the composition b to be tested with the sampling time and the variation trend of the transmittance with the sampling time according to an exemplary embodiment of the present disclosure. DETAILED DESCRIPTION

[0035] In order to make the purpose, technical solution and advantages of the present disclosure clearer, the technical solution of the present disclosure will be clearly and completely described in combination with the embodiments of the present disclosure. Obviously, the described embodiments are only part of the embodiments of the present disclosure, not all of the embodiments. Based on the embodiments in the present disclosure, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present disclosure. It should be noted that the embodiments in the present disclosure and the features in the embodiments can be arbitrarily combined with each other without conflict.

[0036] The toughening of the matrix resin is to add thermoplastic resin toughening particles or toughening agents to the thermosetting resin, and then prepare the composite material from the obtained prepreg. However, in the toughening synthesis process of the matrix resin, there is a problem that the uniformity of dispersion and dissolution of the toughening particles cannot be qualitatively judged. In the related art, the method for judging the degree of dispersion of the toughening particles in the resin is to cover the surface of the paper with letters on it with a resin film dispersed with toughening particles, and observe with the naked eye whether the letters can be clearly observed through the resin. If the letters can be clearly observed, it can be judged that the transparency of the resin synthesis is good, the toughening particles are more evenly distributed, and the degree of dissolution is high; if the letters cannot be clearly observed, it can be judged that the resin needs to be further extended or the dissolution temperature needs to be increased for dispersion and dissolution. This judgment method is inefficient and not accurate enough.

[0037] Based on this, the exemplary embodiment of the present disclosure provides a method for testing the degree of solubility, such as Figure 1 As shown, the test method includes:

[0038] S100, under preset conditions, dispersing toughening particles into a resin composition, and heating the composition to a first preset temperature to form a composition to be tested.

[0039] It should be noted that the test method for the degree of solubility provided by the exemplary embodiment of the present disclosure can be applied to the test of the degree of solubility of toughening particles in a resin composition during the production of resin-based composite materials, that is, directly sampling from the production site of the resin-based composite materials to obtain the composition to be tested. Alternatively, it can also be used to test the degree of solubility of toughening particles in a resin composition during the laboratory simulation of the production of resin-based composite materials, that is, the toughening particles are dispersed and added to the resin composition, and the temperature is raised to a first preset temperature to form a composition to be tested.

[0040] The first preset temperature may be 130±20° C. For example, under preset conditions, after the toughening particles are dispersed and added to the resin composition, the temperature is raised to 130±20° C. at a heating rate of 1.5-2° C. / min to form a composition to be tested.

[0041] The dissolution of toughening particles is divided into three stages: dispersion, swelling and dissolution. The temperature of dispersion and swelling should be maintained at ≤90°C, otherwise the toughening particles will be unevenly dispersed, resulting in the phenomenon of toughening particles clumping. After the dispersion is completed, the toughening particles swell when the absorption of the resin composition reaches a certain level. Without changing the external environmental factors, the toughening particles can remain in a swollen state. As the temperature of the dissolution stage is higher than 100°C, the mobility of the molecular chains of the toughening particles is accelerated, so that the toughening particles continue to absorb the resin composition molecules until the two-phase system of the toughening particles and the resin composition becomes uniform and reaches a state of complete dissolution.

[0042] S200, when the temperature is raised to the first preset temperature, a plurality of samples to be tested are taken out from the composition to be tested in different time periods.

[0043] In step S100, toughening particles are dispersed and added to the resin composition. When the temperature is raised to a preset temperature, a plurality of test samples are taken out from the test composition at different time periods to test the solubility of the toughening particles in the test composition at different time periods, and then determine the time when the solubility of the toughening particles in the test composition reaches the maximum, so as to provide guidance for the production of resin-based composite materials.

[0044] S300, testing the light transmittance of each sample to be tested respectively.

[0045] The transmittance of the composition to be tested is related to the degree of solubility of the toughening particles in the resin composition. The higher the degree of solubility of the toughening particles, the higher the transmittance of the composition to be tested. Therefore, the transmittance of the composition to be tested can characterize the degree of solubility of the toughening particles in the composition to be tested to a certain extent.

[0046] S400, respectively testing the viscosity of each sample to be tested.

[0047] The viscosity of the composition to be tested is related to the degree of solubility of the toughening particles in the resin composition. The higher the degree of solubility of the toughening particles, the higher the viscosity of the composition to be tested. Therefore, the viscosity of the composition to be tested can characterize the degree of solubility of the toughening particles in the composition to be tested to a certain extent.

[0048] S500, determining the dissolution degree of the toughening particles in the composition to be tested according to the transmittance and viscosity of each sample to be tested.

[0049] The transmittance and viscosity of the composition to be tested can characterize the solubility degree of the toughening particles in the resin composition to a certain extent. Therefore, the solubility degree of the toughening particles in the composition to be tested can be determined based on the transmittance and viscosity of the composition to be tested which are easily measured. This method for testing the solubility degree of the toughening particles in the composition to be tested is fast and effective, and the test results are accurate.

[0050] The solubility test method provided by the exemplary embodiment of the present disclosure determines the solubility degree of the toughening particles in the composition to be tested by using the transmittance and viscosity of the composition to be tested which can be easily measured, thereby effectively solving the problem that the solubility degree of the toughening particles in the composition to be tested cannot be qualitatively judged. In addition, the test process is convenient and fast, and the test results are accurate, which can effectively provide guidance for the production process of resin-based composite materials.

[0051] It should be noted that, in the solubility test method provided by the above-mentioned exemplary embodiment of the present disclosure, there is no order of priority between step S300 and step S400, that is, step S300 can be performed first to test the transmittance of each sample to be tested, and then step S400 can be performed to test the viscosity of each sample to be tested, or step S400 can be performed first to test the viscosity of each sample to be tested, and then step S300 can be performed to test the transmittance of each sample to be tested, or the two steps can be performed simultaneously, that is, the transmittance and viscosity of each sample to be tested are tested simultaneously.

[0052] In an exemplary embodiment provided by the present disclosure, the preset conditions include: the second preset temperature is 70-90°C.

[0053] At the second preset temperature of 110-150°C, the viscosity of the resin polymer is low, and the toughening particles to be added can be divided into multiple portions, and the materials can be added in batches at a certain interval, for example, the toughening particles can be dispersed and added to the resin composition in batches while stirring to form a composition to be tested. The interval between two adjacent feedings can be 1-5 minutes to ensure that the toughening particles are evenly dispersed in the composition to be tested.

[0054] In an exemplary embodiment provided by the present disclosure, the resin composition includes at least one of bisphenol A epoxy resin, bisphenol F epoxy resin, bisphenol S epoxy resin, AFG90 epoxy resin, AG80 epoxy resin and aminophenol-based trifunctional epoxy resin.

[0055] When testing the degree of solubility of toughening particles in a resin composition during the production of a resin-based composite material, the components of the resin composition can be formulated according to the formula of the resin-based composite material produced on site. For example, when the resin in the resin-based composite material produced on site includes bisphenol A epoxy resin and bisphenol F epoxy resin, the components of the resin composition can be bisphenol A epoxy resin and bisphenol F epoxy resin, and the mass ratio between bisphenol A epoxy resin and bisphenol F epoxy resin in the resin composition is formulated according to the mass ratio between bisphenol A epoxy resin and bisphenol F epoxy resin in the resin on site.

[0056] In an exemplary embodiment provided by the present disclosure, the toughening particles include at least one of polyetherimide, polyethersulfone, polyphenylene ether, polyimide, polyetheretherketone and polyaryletherketone.

[0057] When testing the degree of solubility of toughening particles in the resin composition during the production of resin-based composite materials, the components of the toughening particles can be formulated according to the formula of the resin-based composite materials produced on site. For example, when the toughening agent in the resin-based composite materials produced on site includes polyethersulfone and polyphenylene ether, the components of the toughening particles can be polyethersulfone and polyphenylene ether, and the mass ratio between polyethersulfone and polyphenylene ether in the toughening particles is formulated according to the mass ratio between polyethersulfone and polyphenylene ether in the toughening agent on site.

[0058] In the exemplary embodiment provided in the present disclosure, the particle size of the toughening particles is 50-500 um.

[0059] In this embodiment, the particle size of the toughening particles is 50-500um, and the particle size distribution of the toughening particles is relatively uniform, which facilitates the dissolution of the toughening particles in the composition to be tested and avoids the toughening particles containing too large or too small particles, which interferes with the test of the solubility degree of the toughening particles in the composition to be tested.

[0060] In an exemplary embodiment provided by the present disclosure, a plurality of samples to be tested are taken out from the composition to be tested at different time periods, including:

[0061] From the composition to be tested, samples to be tested were taken out at 0 min, 20 min, 40 min, 60 min, 80 min and 90 min, respectively.

[0062] The toughening particles are fed in batches, dispersedly added to the resin composition, heated to the first preset temperature, and the composition to be tested is formed. For example, it can be the last time the toughening particles are fed, and the temperature is raised to the first preset temperature. From the composition to be tested, the samples to be tested are taken out at 0min, 20min, 40min, 60min, 80min and 90min, respectively. The taken samples to be tested can be used to characterize the dissolution degree of the toughening particles in the composition to be tested after being dissolved for 0min, 20min, 40min, 60min, 80min and 90min. The samples to be tested taken out at 0min, 20min, 40min, 60min, 80min and 90min are tested for transmittance and viscosity, and the relationship between transmittance-sampling time and / or viscosity-sampling time is established, so as to determine the dissolution degree of the toughening particles in the composition to be tested, and determine the peak time when the dissolution degree of the toughening particles in the composition to be tested reaches the maximum value, providing guidance for the production process of resin-based composite materials.

[0063] In the exemplary embodiment provided by the present disclosure, step S500 determines the degree of dissolution of the toughening particles in the composition to be tested according to the transmittance and viscosity of each sample to be tested, including:

[0064] S510, determining whether the transmittance and viscosity of the composition to be tested satisfy a linear relationship according to the transmittance and viscosity of each sample to be tested.

[0065] According to the transmittance and viscosity of each sample to be tested, determine whether the transmittance and viscosity of the test composition satisfy a linear relationship. If the linear relationship is satisfied, it indicates that the transmittance and viscosity of the test composition have a linear correlation, and the degree of solubility of the toughening particles in the test composition can be determined by the transmittance and viscosity of the test composition.

[0066] S520. When the transmittance and the viscosity satisfy a linear relationship, the dissolution degree of the toughening particles in the composition to be tested is determined according to a preset rule.

[0067] When the transmittance and viscosity satisfy a linear relationship, it indicates that the solubility degree of the toughening particles in the composition to be tested can be determined by the transmittance and viscosity of the composition to be tested. Then, the solubility degree of the toughening particles in the composition to be tested can be determined according to the transmittance and viscosity of each sample to be tested according to preset rules.

[0068] In the exemplary embodiment of the present disclosure, after determining that the transmittance and viscosity of the composition to be tested satisfy a linear relationship, the solubility degree of the toughening particles in the composition to be tested is determined by the easily measurable transmittance and viscosity of the composition to be tested, which effectively solves the problem that the solubility degree of the toughening particles in the composition to be tested cannot be qualitatively judged, and the testing process is convenient and fast, and the test results are accurate.

[0069] In an exemplary embodiment provided by the present disclosure, determining the dissolution degree of the toughening particles in the composition to be tested according to a preset rule in step S520 includes:

[0070] S521, determining the peak time when the transmittance and / or viscosity reaches the peak value.

[0071] The relationship between transmittance-sampling time and / or viscosity-sampling time can be established based on the transmittance and viscosity of each sample taken out at different time periods. When the transmittance and / or viscosity reach the peak time of the peak value, that is, the transmittance and / or viscosity no longer increases with the increase of sampling time, it indicates that the transmittance and / or viscosity has reached the peak value, and the sampling time corresponding to the peak value is the peak time.

[0072] S522. When the dissolution time is greater than or equal to the peak time, the dissolution of the toughening particles in the composition to be tested is complete; the dissolution time includes the time measured from the time when the temperature is raised to the first preset temperature.

[0073] At the peak time, the dissolution of the toughening particles in the composition to be tested reaches the maximum extent, that is, even if the dissolution continues, the dissolution degree of the toughening particles in the composition to be tested will not change, so when the dissolution time (i.e., sampling time) is greater than or equal to the peak time, the dissolution degree of the toughening particles in the composition to be tested is completely dissolved, so the dissolution of the toughening particles in the composition to be tested can be ended at the peak time. The dissolution time (i.e., sampling time) includes the time measured from the time when the temperature is raised to the first preset temperature.

[0074] In the exemplary embodiments of the present disclosure, the degree of dissolution of the toughening particles in the test composition is determined based on the peak time when the transmittance and / or viscosity reach the peak value. That is, the degree of dissolution of the toughening particles in the test composition is determined by the transmittance and viscosity of the test composition that are easily measured. This effectively solves the problem that the degree of dissolution of the toughening particles in the test composition cannot be qualitatively judged, and the test process is convenient and fast, and the test results are accurate.

[0075] In an exemplary embodiment provided by the present disclosure, the method further includes: when the resin composition includes a plurality of resins, mixing the resins at 70-90° C. for 10-30 min to obtain the resin composition.

[0076] When testing the degree of solubility of toughening particles in a resin composition during the laboratory simulation of the production process of a resin-based composite material, the components of the resin composition can be formulated according to the formula of the resin-based composite material produced on site. The resin in the resin-based composite material produced on site can be a single resin or can include multiple resins. Accordingly, the resin composition can also be a single resin or can include multiple resins. In the case where the resin composition includes multiple resins, the resins included in the resin composition are mixed at 70-90°C for 10-30 minutes according to the mass ratio, so that the resins are evenly mixed to obtain a resin composition.

[0077] In the exemplary embodiment provided in the present disclosure, the light transmittance of each sample to be tested is tested respectively, including:

[0078] The transmittance of each sample to be tested was tested by a spectrophotometer at a preset wavelength of 780-390 nm and a scanning speed of 0.5-1 nm.

[0079] In this embodiment, the toughening particles are dispersed and added to the resin composition, and when the temperature is raised to the first preset temperature, a plurality of samples to be tested are taken out from the test composition in time periods, and after taking out the samples to be tested in each time period, the transmittance of the samples to be tested is tested under the conditions of a preset wavelength of 780-390nm and a scanning speed of 0.5-1nm. The transmittance of the test composition is related to the degree of solubility of the toughening particles in the resin composition. The higher the degree of solubility of the toughening particles, the higher the transmittance of the test composition. Therefore, the transmittance of the test sample can characterize the degree of solubility of the toughening particles in the resin composition to a certain extent.

[0080] In the exemplary embodiment provided by the present disclosure, before testing the transmittance of each sample to be tested respectively, the testing method further includes: placing each sample to be tested in a quartz glass cuvette, and placing it in a vacuum oven at 120° C. for vacuum degassing treatment for 5-10 minutes to avoid bubbles blocking the propagation of light during the transmittance test.

[0081] In the exemplary embodiment provided by the present disclosure, the viscosity of each sample to be tested is tested separately, including:

[0082] The viscosity of each sample to be tested was tested by a rheometer at a heating rate of 1-3°C / min and a temperature of 95-110°C.

[0083] In this embodiment, the toughening particles are dispersed and added to the resin composition. When the temperature is raised to the first preset temperature, a plurality of samples to be tested are taken out from the test composition in time periods. After taking out the samples to be tested in each time period, the viscosity of the samples to be tested is tested. During the test, the temperature rise program of the rheometer is 1-3°C / min, the temperature is raised to 95-110°C, the clamp gap is 500-800um, and the viscosity of the samples to be tested is tested in shear mode. The viscosity of the test composition is related to the degree of solubility of the toughening particles in the resin composition. The higher the degree of solubility of the toughening particles, the higher the viscosity of the test composition. Therefore, the viscosity of the test sample can characterize the degree of solubility of the toughening particles in the test composition to a certain extent.

[0084] In order to more clearly explain the technical solution of the present disclosure, two specific examples of the method for testing the degree of solubility provided by the exemplary embodiments of the present disclosure are given.

[0085] Example 1

[0086] The oven was turned on, and the required mixed bisphenol A epoxy resin and AFG90 epoxy resin were placed in the oven and preheated at 80°C for 60 minutes. The preheated bisphenol A epoxy resin and AFG90 epoxy resin were added to the reactor in the order of 30 parts of bisphenol A epoxy resin and 50 parts of AFG90 epoxy resin, and stirred at 80±10°C for 20±10 minutes to obtain a resin composition, and 20 parts of polyethersulfone were added to the reactor in 5 batches within 20 minutes, mixed and dispersed, and heated to 130°C to obtain a composition a to be tested, and the samples to be tested were taken out at 0min, 20min, 40min, 60min, 80min and 90min from the time of heating to 130°C.

[0087] After the sample to be tested is degassed, its transmittance is tested by a spectrophotometer, and then its viscosity is tested by a rheometer to obtain a linear relationship between transparency and viscosity at 100°C, such as Figure 2 shown.

[0088] Figure 2 In the coordinate graph shown, the horizontal axis is the transmittance, the unit is %, and the vertical axis is the viscosity, the unit is Pa·s. Figure 2 It can be seen that the transmittance and viscosity of the composition a to be tested show a certain linear relationship, the linear equation is y = 1.1206x + 7.1505, and the linear correlation coefficient R 2 It is 0.9954, and the correlation is high. Figure 3 The viscosity versus sampling time trend curve 10 and the transmittance versus sampling time trend curve 20 are shown in FIG. Figure 3 The horizontal axis in the figure is the sampling time in min, the vertical axis on the left is the transmittance in %, and the vertical axis on the right is the viscosity in Pa·s. Figure 3 It can be seen that with the increase of sampling time, the toughening particles gradually begin to dissolve in the test composition a, and the transmittance and viscosity of the test composition a also show a gradually increasing trend. When the sampling time reaches 60min, its transmittance and viscosity basically reach the highest value and tend to be stable. Therefore, for the test composition a formula, during the synthesis process, when the transmittance of the test composition a is ≥93%, the dissolution degree of the toughening particles reaches the best state. Accordingly, under the test composition a formula, during the synthesis process of the test composition a, it can be determined that the toughening particles are basically dissolved according to the transmittance of the test composition a being above 93%.

[0089] Example 2

[0090] The oven was turned on, and the required mixed bisphenol F epoxy resin, AG80 epoxy resin and AFG90 epoxy resin were placed in the oven and preheated at 80°C for 60 minutes. The preheated bisphenol F epoxy resin, AG80 epoxy resin and AFG90 epoxy resin were added to the reactor in the order of 35 parts of bisphenol F epoxy resin, 20 parts of AG80 epoxy resin and 30 parts of AFG90 epoxy resin, and stirred at 80±10°C for 20±10 minutes to obtain a resin composition, and 15 parts of polyethersulfone were added to the reactor in 5 batches within 20 minutes, mixed and dispersed, and heated to 130°C to obtain a composition b to be tested. From the time of heating to 130°C, the samples to be tested were taken out at 0min, 10min, 30min, 50min, 70min and 90min.

[0091] After the sample to be tested is degassed, its transmittance is tested by a spectrophotometer, and then its viscosity is tested by a rheometer to obtain a linear relationship between transparency and viscosity at 100°C, such as Figure 4 shown.

[0092] Figure 4 In the coordinate graph shown, the horizontal axis is the transmittance, the unit is %, and the vertical axis is the viscosity, the unit is Pa·s. Figure 4 It can be seen that there is a certain linear relationship between the transmittance and viscosity of the composition b to be tested, the linear equation is y=0.9441x+9.4149, and the linear correlation coefficient R 2 It is 0.9878, and the correlation is high. Figure 5 The curve 30 showing the variation trend of transmittance with sampling time and the curve 40 showing the variation trend of viscosity with sampling time are shown in FIG. Figure 5 The horizontal axis in the figure is the sampling time in min, the vertical axis on the left is the transmittance in %, and the vertical axis on the right is the viscosity in Pa·s. Figure 5 It can be seen that with the increase of sampling time, the toughening particles gradually begin to dissolve in the test composition b, and the transmittance and viscosity of the test composition b also show a gradually increasing trend. When the sampling time reaches 50min, its transmittance and viscosity basically reach the highest value and tend to be stable. Therefore, for the test composition b formula, during the synthesis process, when the transmittance of the test composition b is ≥90.5%, the dissolution degree of the toughening particles reaches the best state. Accordingly, under the test composition b formula, during the synthesis process of the test composition b, it can be determined that the toughening particles are basically dissolved according to the transmittance of the test composition b being above 90.5%.

[0093] The contents described above may be implemented individually or in combination in various ways, and these variations are all within the protection scope of the present disclosure.

[0094] Finally, it should be noted that in this article, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or apparatus that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or apparatus.

[0095] The above embodiments are only used to illustrate the technical solutions of the present disclosure, rather than to limit them. Although the present disclosure is described in detail with reference to the above embodiments, a person skilled in the art should understand that the technical solutions described in the above embodiments can still be modified, or some of the technical features can be replaced by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the spirit and scope of the technical solutions of the embodiments of the present disclosure.

Claims

1. A method for testing the degree of solubility, characterized in that: The test method includes: Under preset conditions, the toughening particles are dispersed and added into the resin composition, and the temperature is raised to a first preset temperature to form a composition to be tested; When the temperature is raised to the first preset temperature, a plurality of samples to be tested are taken out from the composition to be tested in different time periods; Testing the light transmittance of each of the samples to be tested respectively; Testing the viscosity of each of the samples to be tested respectively; The dissolution degree of the toughening particles in the composition to be tested is determined according to the transmittance and viscosity of each of the samples to be tested.

2. The method for testing the degree of solubility according to claim 1, characterized in that: The step of determining the dissolution degree of the toughening particles in the composition to be tested according to the transmittance and viscosity of each of the samples to be tested comprises: Determining whether the transmittance and the viscosity of the composition to be tested satisfy a linear relationship according to the transmittance and the viscosity of each of the samples to be tested; When the transmittance and the viscosity satisfy the linear relationship, the dissolution degree of the toughening particles in the composition to be tested is determined according to a preset rule.

3. The method for testing the degree of solubility according to claim 2, characterized in that: The step of determining the dissolution degree of the toughening particles in the composition to be tested according to a preset rule comprises: Determining the peak time when the transmittance and / or the viscosity reaches a peak value; When the dissolution time is greater than or equal to the peak time, the dissolution of the toughening particles in the composition to be tested is complete; the dissolution time includes the time measured from the time when the temperature is raised to the first preset temperature.

4. The method for testing the degree of solubility according to claim 1, characterized in that: The preset conditions include: the second preset temperature is 70-90°C.

5. The method for testing the degree of solubility according to any one of claims 1 to 4, characterized in that: The resin composition comprises at least one of bisphenol A epoxy resin, bisphenol F epoxy resin, bisphenol S epoxy resin, AFG90 epoxy resin, AG80 epoxy resin and aminophenol-based trifunctional epoxy resin; and / or, The toughening particles include at least one of polyetherimide, polyethersulfone, polyphenylene oxide, polyimide, polyetheretherketone and polyaryletherketone.

6. The method for testing the degree of solubility according to any one of claims 1 to 4, characterized in that: The particle size of the toughening particles is 50-500um.

7. The method for testing the degree of solubility according to any one of claims 1 to 4, characterized in that: The method of taking out a plurality of samples to be tested from the composition to be tested in different time periods comprises: The samples to be tested were taken out from the composition to be tested at 0 min, 20 min, 40 min, 60 min, 80 min and 90 min, respectively.

8. The method for testing the degree of solubility according to any one of claims 1 to 3, characterized in that: The method further comprises: when the resin composition comprises a plurality of resins, mixing the resins at 70-90° C. for 10-30 minutes to obtain the resin composition.

9. The method for testing the degree of solubility according to claim 1, characterized in that: The light transmittance of each of the samples to be tested is tested separately, comprising: The transmittance of each of the samples to be tested was tested by a spectrophotometer at a preset wavelength of 780-390 nm and a scanning speed of 0.5-1 nm.

10. The method for testing the degree of solubility according to claim 1, characterized in that: The method of testing the viscosity of each of the samples to be tested comprises: The viscosity of each of the samples to be tested was tested by a rheometer at a heating rate of 1-3°C / min and at a temperature of 95-110°C.